Round bale alfalfa processing method does not influence feeding or mixing characteristics in a total mixed ration - Jones, S.Q.; Marston, T.T.; Kraus, T.J.; DeRouchey, Joel M.; Waggoner, Justin W.; Breiner, Ryan M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Nutritionists and producers often assume that ingredients in a total mixed ration are uniformly mixed. However, many factors may affect ration homogeneity, including particle size, shape, and density and mixer discharge location. Forages are often ground prior to mixing in a total mixed ration to reduce variation in forage particle length. However, preprocessing forages while baling may facilitate particle length reduction and eliminate the need to grind forages prior to mixing. Objectives of this study were to determine the effects of forage processing method on uniformity and particle length of the total mixed ration at different discharge locations throughout mixing.
Keywords: Beef; Alfalfa; Total mixed ration; Forage